Evaluación de diferentes sustratos para la producción de plantines de caoba en la fase de vivero en el cantón Marcabelí - Chamba Sarango, Tatiana Beatriz (Machala : Universidad Técnica de Machala, 2022)
Honduran mahogany is a forest species that belongs to the Meliaceae family, its origin is from Central America, reaching South America. It is considered an important timber species because its wood is hard and has a characteristic reddish color that is highly valued both in the national and international markets. It should be noted that it also has medicinal and handicraft uses. In Ecuador, the largest production is found in the Amazon region and to a lesser extent in the coastal region. Among its botanical characteristics is the great height that can reach up to 50 meters and a stem diameter that exceeds 2 meters. Currently, mahogany has been threatened by indiscriminate logging. The research was carried out in the cantón Marcabelí ; province of El Oro, in order to verify the response of growth and development of the Honduran mahogany forest species to the use of four different substrates in the nursery stage. To evaluate the results in the different substrates used, a completely randomized design with four treatments and four replications was applied. The designated treatments were T1. Black soil 100%, T2. Black soil 60%, River sand 30%, Worm castings 10%, T3. Black soil 30%, River sand 60%, Earthworm humus 10%, T4. Black soil 40%, river sand 40%, earthworm humus 20%. The following variables were observed: germination percentage, number of leaves, height and stem diameter. A one-factor analysis of variance (ANOVA) was performed on each of the variables to verify whether or not there were significant statistical differences, using tests of ranges and multiple comparisons (post-hoc tests) and the non-parametric Kruskal-Wallis test when the variable does not follow a normal distribution. The results obtained for the germination percentage show that the substrate with the highest germination percentage is 100% black soil. In the variable stem height, the substrate mixture Black soil 40%, River sand 40%, Worm castings 20%, obtained the greatest length at 46, 56 and 66 days after sowing, the substrate Black soil 100% obtained the greatest height at 76 days, as for the diameter of the stem, it was greater in the substrate Black soil 100% at 46 and 56 days, while at 66 and 76 days the substrate mixture in which the diameter was greater was Black soil 40%, River sand 40%, Worm castings 20%. The substrate mixture in which a greater number of leaves was obtained at 46,66 and 76 days was the substrate mixture corresponding to Black soil 40%, River sand 40%, Worm castings 20%, presenting in substrate Black soil 100% the greatest number of leaves at 56 days after sowing, so it is concluded that the substrate in which a greater percentage of germination is achieved is using Black soil 100%, and to achieve greater growth and development of mahogany seedlings the substrate that presented better results was: Black soil 40%, River sand 40%, Earthworm humus 20%.
La caoba hondureña es una especie forestal que pertenece a la familia Meliaceae, su origen de desplaza desde Centro América llegando hasta Sudamérica, es considerada una importante especie maderable ya que su madera es dura y tiene un color característico rojizo muy cotizada tanto en el mercado nacional como internacional. Cabe recalcar que además tiene usos medicinales y artesanales. En Ecuador se presenta la mayor producción en la región Amazónica y en menos proporción en la región Costa. Entre sus características botánicas destaca la gran altura que puede alcanzar llegando hasta 50 metros y un diámetro del tallo que supera los 2 metros. En la actualidad la caoba ha sido amenazada por la tala indiscriminada de bosques. La investigación se realizó en el cantón Marcabelí; provincia de El Oro, con el fin de comprobar la respuesta de crecimiento y desarrollo de la especie forestal caoba hondureña ante el uso de cuatro sustratos diferentes en la etapa de vivero. Para evaluar los resultados en los diferentes sustratos utilizados se aplicó un diseño completamente al azar cuatro tratamientos con cuatro repeticiones. Los tratamientos designados fueron T1. Tierra negra 100%, T2. Tierra negra 60%, Arena de río 30%, Humus de lombriz 10%, T3. Tierra negra 30%, Arena de río 60%, Humus de lombriz 10%, T4. Tierra negra 40%, Arena de río 40%, Humus de lombriz 20%. Las variables que se observaron son las siguientes: porcentaje de germinación, número de hojas, altura y diámetro del tallo. Se realizó un análisis de varianza (ANOVA) de un factor en cada una de las variables, para verificar si se presentaron o no diferencias estadísticas significativas, se aplicó pruebas de rangos y comparaciones múltiples (pruebas Post-hoc) y prueba no paramétrica Kruskal-Wallis cuando la variable no sigue una distribución normal. Los resultados alcanzados referente al porcentaje de germinación, demuestran que la utilización del sustrato que presenta un mayor porcentaje de germinación es Tierra negra 100%. En la variable altura del tallo la mezcla de sustrato Tierra negra 40%, Arena de río 40%, Humus de lombriz 20%, es la que obtuvo una mayor longitud a los 46, 56 y 66 días después de la siembra, el sustrato Tierra negra 100% obtuvo la mayor altura a los 76 días, en cuanto al diámetro del tallo fue mayor en el sustrato Tierra negra 100% a los 46 y 56 días, mientras que a los 66 y 76 días la mezcla de sustrato en la que fue mayor el diámetro es Tierra negra 40%, Arena de río 40%, Humus de lombriz 20%. La mezcla de sustrato en la que se obtuvo un mayor número de hojas a los 46,66 y 76 días fue la mezcla de sustrato que corresponde a Tierra negra 40%, Arena de río 40%, Humus de lombriz 20%, presentando en sustrato Tierra negra 100% el mayor número de hojas a los 56 días después de la siembra, por lo que se concluye que el sustrato en el que se logra un mayor porcentaje de germinación es utilizando Tierra negra 100%, y para lograr mayor crecimiento y desarrollo de los plantines de caoba el sustrato que presentó mejores resultados fue: Tierra negra 40%, Arena de río 40%, Humus de lombriz 20%.
Keywords: CAOBA; HONDUREÑA; SUSTRATOS; PLÁNTULAS